PENERAPAN MODEL PEMBELAJARAN NUMBER HEADS TOGETHER PADA PEMBELAJARAN GEOGRAFI KELAS XI IPS SMA NEGERI 2 SAMBAS - Zulkid, Lutfi; Buwono, Sri; Anasi, Putri Tipa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe purpose of this research is to know the effect from the use of Number Heads Together (NHT) learning model to students' learning achievement in Geography lesson on the eleventh grade Social class in SMA Negeri 2 Sambas. The learning method that used in this research was Quasi Experimental design, Non-equivalent Control Group design. The participant of this research were eleventh grade Social 4 class that consist of thirty students and eleventh grade Social 2 class that consist of thirty three students. The research instrument that used in this research was multiple choice test that consist of fifty questions. The result showed that there was a difference on the students' learning achievement before and after the treatment. It was proven by the pretest mean score before using the Number Heads Together (NHT) learning model, which was 64,30. The students' posttest mean score that were given the treatment by using Number Heads Together (NHT) learning model had improved, which was 77,10 and the distribution data was normal after conducting the normality test. Based on the research findings, on the paired sample t-test, the test showed that the t-ratio score was higher than t-critical score (2,255 > 1,670), indicated that H0 was rejected and HA was accepted. Based on the calculation of the effect size, the score was 0,542 (medium criteria). This result indicated that there was a medium effect between the use of Number Heads Together (NHT) learning model to students' learning achievement on the eleventh grade Social class in SMA Negeri 2 Sambas in Geography lesson.Keywords : Number Heads Together (NHT) learning model, Learning Achievement